1968
DOI: 10.1192/bjp.114.511.733
|View full text |Cite
|
Sign up to set email alerts
|

Functional Psychoses and Social Status

Abstract: The relationship between mental disorder and social background has for many years attracted the interest of epidemiologically oriented psychiatrists. Investigations in several countries have demonstrated that patients admitted to mental hospitals are recruited to a large degree from the lower social strata of society, but there is still a vast difference of opinion in so far as interpretations of these findings are concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Numerous studies indicate that individuals with low social standards, income and prestige have increased psychiatric morbidity, in particular schizophrenia and vice versa. As regards patients with delusional psychosis these seem to be recruited from the lower social groups too (3, 4, 16,17), as the results of the present study show. During the observation period a slight downlift mobility was demonstrated.…”
Section: Discussionsupporting
confidence: 53%
“…Numerous studies indicate that individuals with low social standards, income and prestige have increased psychiatric morbidity, in particular schizophrenia and vice versa. As regards patients with delusional psychosis these seem to be recruited from the lower social groups too (3, 4, 16,17), as the results of the present study show. During the observation period a slight downlift mobility was demonstrated.…”
Section: Discussionsupporting
confidence: 53%
“…Dunham (1964) found no significant differences in the mobility patterns of 52 schizophrenics, 69 cases of affective disorder and neurosis, and 54 cases of character disturbance and acting out disorders, but did not have a general population control sample. Griinfeld and Salvesen (1968), using Norwegian census figures to provide expected distributions of social class of patients and of their parents, found that both schizophrenics and reactive psychotics-that is, psychotic reactions in psychopathic individuals-showed a social status decline when compared with fathers, as well as with the expectation for those of same age in the average population. At follow-up, which was at least five years after primary admission, the schizophrenics showed a marked additional social 'down drift' in contrast with the reactive psychotics, who tended to remain almost on the same levels.…”
Section: Comparable Studiesmentioning
confidence: 96%
“…Although studies examining patients' SES have generally agreed that low SES is associated with higher risk for schizophrenia, studies examining parental or childhood SES have been inconclusive. 1,2 While some studies have indicated that growing up in a low SES environment is associated with increased risk for schizophrenia, [3][4][5][6][7][8][9] others have found no such effect, [10][11][12][13][14] and still others have reported that growing up in a high SES environment may be associated with higher risk for schizophrenia [15][16][17][18] (see table 1 for a summary of previous studies which examined childhood SES). The objective of the current study was to address this controversial issue by examining the association between SES and risk of hospitalization for schizophrenia in a large population-based sample of Israeli adolescents assessed by the Israeli military draft board before the onset of illness, then followed for later hospitalization for schizophrenia using a national psychiatric hospitalization registry.…”
Section: Introductionmentioning
confidence: 99%